Antegrade Endobiliary Forceps Biopsy Improves Diagnosis of Klatskin Tumor Compared to Brush Biopsy - A. V. Kozlov; P. G. Tarazov; A. A. Polikarpov; A. V. Moiseenko; A. I. Urbansky; M. V. Yutkin; G. M. Yakshieva; D. A. Granov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. To evaluate the safety and accuracy of percutaneous transhepatic biliary biopsy in patients with suspected Klatskin tumor.Materials and methods. Between 2013–2020, percutaneous transhepatic biliary drainage (PTBD) was performed in 52 patients with Klatskin tumor, complicated by obstructive jaundice. After successful PTBD, the diagnosis was verified by antegrade access. 74 procedures were performed: brush (n = 36; 48.6 %) or forceps biopsies (n = 38; 51.4 %).Results. There were no adverse events associated with a brush biopsy. Only grade I complications were after the forceps technique: 3 patients (7.9 %) developed hemobilia, which was corrected conservatively. Malignant lesions of the biliary tract were detected by forceps technique in 79.0 %, brush biopsy in 66.7 % (p >0,05). The degree of tumor differentiation was determined in 60.0 % (n = 18) vs 12.5 % (n = 3) (p < 0,01), respectively.Sensitivity and specificity of forceps biopsy were slightly higher than in brush: 82.4 % and 75.0 % vs 73.3 % and 66.7 % (p >0,05).Conclusions. Antegrade percutaneous transhepatic biliary biopsy is safe for both brush and forceps techniques. However, forceps biopsy has higher sensitivity and specificity in the diagnosis Klatskin tumor and better possibility of determining the degree of malignancy differentiation.